REFORMASI PELAYANAN PUBLIK DI DPMPTSP KOTA BENGKULU - Novliza Eka Patrisia; Faizal Anwar (JOPPAS: Journal of Public Policy and Administration Silampari, 2021)
This study aims to determine the implementation and aspects that hinder public service reform in Bengkulu City DPMPTSP in achieving excellent service. The method used in this research is a qualitative method with descriptive analysis. The results of the study indicate that services at DPMPTSP already cover 10 aspects of public services such as simplicity, clarity, certainty, security, responsibility, completeness of facilities and infrastructure, ease of access, discipline, and comfort. While the inhibiting aspects such as the completion of long licensing times, maintenance of facilities and infrastructure, lack of parking space, not all people use the website portal. The conclusion of this study is that the implementation of service reform in DPMPTSP has shown excellent service and aspects that need to be improved such as maximizing the use of technology, discipline, and completeness of facilities and infrastructure. Keywords: Administrative Reform, Governance, Public service.